Spatial patterns of crimes in Klaipėda and their assessment in social geographic approach - SPIRIAJEVAS, EDUARDAS; BETEIKA, LAIMONAS (Kriminologijos studijos, 2015)
This article explores spatial patterns of crimes, their dynamics in structure, time and space since 1990 until 2010 in Klaipėda, Lithuania. A period of research involves the changes during the post-soviet time. The research is combined of two sets of data. One set combined by social geographic indicators (changes of population, unemployment, crimes and their structure, and social geographic features as density of crimes, distribution of spatial patterns of crimes). Another set of data combined by geo-information of main categories of crimes (thefts, robberies, criminal damages, hooliganism, extortions, grievous and intending bodily harms, producing and selling of narcotics and homemade alcohol, sexual assaults). The Kernel method was used as a key measure to estimate the changes of spatial patterns of crimes with their geographic shapes, scopes and density. The data was processed with Geographic Information Systems (GIS) and elaborated in cartographic representations. The research determined that a majority of criminal activities are mostly located along the main streets and around shopping centres. The distribution of criminal activities is explained by the concepts of opportunity theory and daily routine theory. Despite the changes of crime rates and unemployment, segregation of society and shrinking of urban population in Klaipėda city, the spatial patterns of crimes over the two decades were distributed more extensively but with lower density.